1345. The Cascade of Care for Early Infant Diagnosis in Zimbabwe: Point of Care HIV Testing at Birth and 6-8 weeks. (15th December 2022) - Aitcheson, Nancy; Sacks, Emma; Cohn, Jennifer
Abstract: Background: Routine birth testing of HIV exposed infants (HEI) using point of care (POC) nucleic acid testing may allow for earlier diagnosis and treatment of HIV-infected infants than current methods, but more data are needed on retention in care for those diagnosed as HIV-positive at birth and on re-testing for those with a negative HIV test at birth. Methods: POC birth testing (within 48 hours of birth) was offered to all HEI born at ten public maternities in Zimbabwe from November 2018 to July 2019. Data from routine registers, including information on re-testing at 6–8 weeks for infants testing HIV-negative at birth and six-month retention in care among infants testing HIV-positive at birth. Results: Of 2, 854 eligible HEI, 2, 806 (98.3%) received a POC HIV birth test. We identified 39 HIV-infected infants (1.4%), and 23 (59%) were started on ART. Of those, 20 infants (87%) remained on ART at six months. Of the 2, 694 infants who tested negative at birth, 1, 229 (46.5%) had a documented re-test at 6-8 weeks, and 7 (0.6%) of those infants tested positive. Conclusion: Uptake of POC birth testing was high in the 10 study facilities. However, ART initiation for HIV-positive infants was low. Among infants initiated on ART, most but not all continued ART at 6 months. Among infants who tested negative at birth, rates of testing at 6-8 weeks of life were similar to national rates of testing at the same age without a birth test (56%). Improving infant HIV testing rates at 6-8 weeks, regardless of birth testing, should be a priority. Additionally, insuring that HIV-positive newborns are started and retained on ART is critical for preventing morbidity and mortality among HIV-infected infants. Disclosures: All Authors : No reported disclosures.